Dwarf geckos and giant rivers: The role of the São Francisco River in the evolution of Lygodactylus klugei (Squamata: Gekkonidae) in the semi-arid Caatinga of north-eastern Brazil - Lanna, Flávia Mól; Gehara, Marcelo C.M.; Werneck, F. P.; Fonseca, Emanuel M.; Colli, Guarino R.; Sites, Jack Walter; Rodrigues, Miguel Trefaut; Garda, Adrian Antonio (Biological Journal of the Linnean Society, 2020)
Species diversification can be strongly influenced by geomorphological features, such as mountains, valleys and rivers. Rivers can act as hard or soft barriers to gene flow depending on their size, speed of flow, historical dynamics and regional topographical characteristics. The São Francisco River (SFR) is the largest perennial river in the Caatinga biome in north-eastern Brazil and has been considered a barrier to gene flow and dispersal. Herein, we evaluated the role of the SFR on the evolution of Lygodactylus klugei, a small gecko from the Caatinga. Using a single-locus species delimitation method (generalized mixed Yule coalescent), we defined lineages (haploclades). Subsequently, we evaluated the role of the SFR in structuring genetic diversity in this species using a multilocus approach to quantify migration across margins. We also evaluated genetic structure based on nuclear markers, testing the number of populations found through an assignment test (STRUCTURE) across the species distribution. We recovered two mitochondrial lineages structured with respect to the SFR, but only a single population was inferred from nuclear markers. Given that we detected an influence of the SFR only on mitochondrial markers, we suggest that the current river course has acted as a relatively recent geographical barrier for L. klugei, for ~450 000 years. © 2019 The Linnean Society of London, Biological Journal of the Linnean Society.
Keywords: Common Ancestry; Evolution; Gene Flow; Genetic Marker; Genetic Structure; Hypothesis Testing; Lizard; Dna, Mitochondrial; Sao Francisco River; Gekkonidae; Lygodactylus; Sphaerodactylus; Squamata